Double-site defect passivation of perovskite film via fullerene additive engineering toward highly efficient and stable bulk heterojunction solar cells. (August 2021) - Jia, Lingbo; Huang, Fanyang; Ding, Honghe; Niu, Chuang; Shang, Yanbo; Hu, Wanpei; Li, Xingcheng; Yu, Xin; Jiang, Xiaofen; Cao, Ruiguo; Zhu, Junfa; Wang, Guan-Wu; et al.
Highlights: A novel multifunctional fullerene derivative additive (C60 -PyF15) enables double-site defect passivation of perovskite film. The C60 -PyF15 can provide a built-in electric field to improve carrier density and decrease nonradiative recombination. A highest PCE of 20.10% was achieved for the inverted fullerene-incorporated CH3 NH3 PbI3 BHJ-PVKSCs with remarkable stability. Graphical Abstract: Double-site defect passivation of perovskite film was achieved by a perfluoroalkyl and pyridine-cofunctionalized fullerene derivative additive (C60 -PyF15), fulfilled by the coordination interaction of the pyridine moiety with Pb 2+ ions and hydrogen bonding between the fluorine atom within the perfluoroalkyl group and the CH3 NH3 + cations. This resulted in a champion power conversion efficiency of 20.10%, which is among the highest values for fullerene-incorporated inverted bulk heterojunction (BHJ) perovskite solar cells (PVKSCs). ga1 Abstract: Bulk heterojunction (BHJ) perovskite solar cells (PVKSCs) are advantageous in passivating defects and facilitating electron extraction/transport. Most of the reported fullerene derivatives involved in BHJ-PVKSCs render single-site interactions, limiting their passivation effect. Herein, we developed a perfluoroalkyl and pyridine-cofunctionalized fullerene derivative (C60 -PyF15), and applied it as an additive of CH3 NH3 PbI3 layer to construct inverted (p-i-n) BHJ-PVKSCs, affording double-site defect passivation of perovskite film and a champion power conversion efficiency of 20.10%, which is among the highest values for fullerene-incorporated inverted BHJ-PVKSCs. To elucidate the crucial role of the perfluoroalkyl group in efficiency enhancement, another analogous novel non-fluoro-substituted pyridine-functionalized fullerene derivative with the same chain length of alkyl group (C60 -PyH15) was also synthesized, which afforded a champion PCE of 19.22% and is lower than that of C60 -PyF15. The double-site defect passivation ability of C60 -PyF15 is resulted from the coordination interaction of the pyridine moiety with Pb 2+ ions and hydrogen bonding between the fluorine atom within the perfluoroalkyl group and the CH3 NH3 + cations. These enable ordered orientation of CH3 NH3 + and suppressed ion migration, leading to efficiency enhancement and improved ambient and thermal stabilities.